Rural Livelihood Transformations and Land Inequality in Bangka - Westi Utami; M. Nazir Salim; Kistie Lendra Octora; Kholfa Anisa (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Since the Dutch colonial era, Bangka Belitung Province has been a rich province due to its abundanttin mining resources. However, the limitation of tin availability and the extraordinary environmental degradation caused by mining has changed people’s lives. This study aims to determine the level of land ownership inequality and the factors that influence such inequality. In addition, this study also describes the transformation causes of the livelihoods of the majority of the population in Bangka. This research was conducted through descriptive quantitative analysis, and the data was obtained through a survey of 140 head of households whowork as farmers or work as a farm labourers in Bangka and West Bangka. Analysisof land ownership inequality is done through the Gini index ratio measured using the Lorenz curve. The results of a study conducted on 140 respondents in Bangka and Bangka Barat show that the level of land ownership inequality reaches 0.45. Several things have an effect on the level of inequality. First, most of Bangka regions, almost 3/4 the areas have mining permits. Second, there has been a large-scale expansion of oil palm plantations and a lot of Cultivation Rights Permits/HGU. Third, most of the areas outside the mining and the cultivation rights permits are forest areas. The results of the study also show that the majority of the community shifted from miners to farmers due to limited tin sources and low tin prices. The high level of inequality in land ownership and the shifting of community’s main jobs can certainly affect the economic growth which is getting weaker and widening the inequality.